Gender equity in sport from the perspective of European women athletes and sport managers, physical education teachers and sport coaches - Vaquero-Cristóbal, Raquel; Mateo-Orcajada, Adrián; Dağlı Ekmekçi̇, Yeter Aytül; Pereira, Antonino; Amin, Shirin; Meroño, Lourdes; González-Gálvez, Noelia; Ballı, Özgür Mülazımoğlu; Mendes, Francisco; Mbah, Orlando; Abenza-Cano, Lucía; Leiva-Arcas, Alejandro; et al. (Frontiers in Psychology, 2024)
Introduction For years, gender inequality has conditioned women’s participation in sport, exposing them to difficult situations and numerous barriers to face. However, no previous research has analyzed the situation of women in sport from the perspective of the athletes themselves, or from the perspective of the coaches, teachers or managers who work with them. Methods This study examines the perspectives of European women athletes, sports managers, physical education teachers, and sports coaches, on gender equity in sports across six European countries: Greece, Ireland, Italy, Portugal, Spain, and Turkey. The research design was consistent with a critical realist epistemology, and the sampling method was non-probabilistic by convenience. A total of 42 female athletes (mean age: 24.37 ± 8.27 years old; mean sport experience: 6.67 ± 7.76 years) and 45 sports managers, physical education teachers or coaches (mean age: 47.00 ± 11.99 years old; mean sport experience: 9.62 ± 10.60 years), participated in six focus groups in the same countries, in groups of 6 to 10 participants per focus group. Focus groups were conducted to stimulate collective discussions, build upon and question ideas, and reach a consensus on questions drawn up by a group of experts, following previous methodologies. The data analysis involved transcribing, translating, and contextualizing the focus group recordings into English. Inductive thematic analysis, reflexive thematic analysis, and codes and themes within the data were created using NVivo 12 Pro. Results The main topics discussed by the female athletes were “gender inequality in general and in sport,” “barriers to gender equity,” “reasons for abandonment,” “needs,” “environment role models” and “tools for the gender equity in sport.” The main topics discussed by the sports managers, physical education teachers, and coaches were “gender inequality in general,” “gender inequality in sports,” “tools” and “reasons, motives, drivers.” The results of the study revealed that gender inequality in sports is influenced by a broader social context, where stereotypes, biases, and discrimination persist. The participants also highlighted the challenges, barriers, and needs that women athletes face in their careers, such as a lack of resources, support, visibility, and recognition. Moreover, the participants suggested some strategies to promote gender equity in sports, such as increasing investment, awareness, and education, creating policies and legislation, fostering women’s leadership and role modeling, and developing mixed and inclusive sports projects. Discussion According to athletes and sports managers/teachers/coaches, gender inequality is still present in sport. There are barriers and challenges that need to be addressed such as lack of resources, visibility, and recognition for female athletes. Among the strategies that can be used to reverse this situation are increasing investment, awareness, and education, creating policies and legislation, fostering women’s leadership, and developing mixed and inclusive sport projects.